Cerebral Ischemia - Pluta, Ryszard (Exon Publications, 2021)
Cerebral ischemia is one of the most common causes of dementia, which develops in more than half of patients after an ischemic episode. The main mechanism is thought to be pathological changes in the hippocampus, especially in the CA1 area, underlying episodic memory impairment, which is the earliest and most important clinical symptom of post-ischemic dementia. The 13 chapters of this book present a new picture of ischemic brain disease, synthesizing the latest data on disease mechanisms, care for patients with this disease, and potential therapeutic targets. The authors present the characteristics of cerebral ischemia from pregnancy and childhood through adolescence to adulthood. The first two chapters provide a snapshot of the anatomy of the cerebral cortex and the hippocampus, the most affected brain structures after cerebral ischemia. This is followed by nine chapters that present a comprehensive view of the pathological mechanisms of cerebral ischemia, and how a deep understanding of these pathomechanisms hold the key for the discovery and development of novel therapies to help patients affected by cerebral ischemia. Chapter 12 shares real-life experience and challenges of rehabilitating patients into the community after cerebral ischemia, and chapter 13 analyzes the social risk variations, including gender inequality, in the reintegration of post-ischemic stroke patients. Although primarily aimed at scientists and clinicians, the contents of the book will be of interest to all those who are interested in cerebral ischemia, including patients and their caregivers.